Perilaku Politik Pemilih Perempuan Pada Pemilihan Umum Legislatif Tahun 2014 (Studi Di Kelurahan Muka Kuning, Kecamatan Sei Beduk, Kota Batam) - linayati lestari (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2017)
Female voters is one of the electoral contestants were positively correlated with the quality of the policy according to the needs of women where women voters were significant in Muka Kuning village in the ratio of female voters and men are 32.254: 29.131 with the majority of women work as industrial workers. The purpose of this study was to determine the political behavior of women voters, and factors influencing the legislative elections in 2014 in the village of Sei Muka Kuning Batam drum method mixed method, with quota sampling technique to women voters at polling stations at Muka Kuning village. Factors affecting the behavior of individuals and organizations are factors which the individual factors significantly more than the organizational factors. Ex political behavior of female voters. Mostly women at Muka Kuning as moderate voters, namely the ability to reflect on themselves well, internal control center, Personality High mach, investment organizations, alternative occupations are believed to exist, and the hope of success. While the factors that are included in the organization is a reallocation of resources, promotion opportunities, low confidence, role ambiguity, performance evaluation system is not clear, practices a zero-sum remuneration, democratic decision-making, high-performance pressure, and senior managers selfish. This study hasreinforced the theory that Robin jugde individual factors and organiassi shaping the political behavior of women voters at Muka Kuning village conservative. This is affecting for 8889 women voters at Legisltaif elections in 2014.